Abnormal Dentition in a Boy with Incontinentia Pigmenti: Case Report - Afshar, H. (Tehran University of Medical Sciences, 2012)
Incontinentia pigmenti (IP) is an X-linked dominant genodermatosis characterized by typical skin lesions along Blaschko’s lines and associated with ocular, dental, nails, hair, skeletal, central nervous system and cardiovascular anomalies. We report a 5-year-old boy with cutaneous hyperpigmentation along Blaschko’s lines, atrophic streaks, strabismus and mental retardation. He showed the characteristic abnormal dentition seen in IP as partial hypodontia, peg-shaped anterior teeth and un-erupted teeth. The expression of IP in boys is exceptional as the disease is lethal in males.